Twister [videorecording (Blu-Ray)] - Crichton, Michael, 1942-2008; Martin, Anne-Marie, 1957-; Hunt, Helen, 1963-; Paxton, Bill; Elwes, Cary, 1962-; Gertz, Jami; Green, Jack N., 1946-; Mancina, Mark (Warner Home Video, 2008)
Scientists pursue the most destructive weather front to sweep through mid-America's Tornado Alley in 50 years.